Diferentes dosis de nitrógeno en el comportamiento agronómico de dos híbridos de maíz amarillo (Zea mays L.) en el cantón Quinindé. - Troya Herrera, Jacinto Catalino (2015)
This test was performed at the Experimental farm "The future" Mr Urban Troy, located in the northern province of Esmeraldas, with the geographical coordinates of 00 ° N latitude 19'10'' 78 ° 26¨00' 'w The objective of this work was to establish the effects of treatments on the agronomic performance and yield of the hybrid under study and identify the most appropriate dose of nitrogen fertilization, according to the soil conditions in the area. A factorial arrangement (2x3 + 2) arranged in experimental design completely randomized (DBCA) with 8 treatments and 4 replications was used blocks. To establish the differences between treatment means the Tukey test at 0.05% level and the coefficient of variation was used is expressed in percentage. The variables were analyzed: height of intersection of the cob, plant height, number of pods harvested, diameter and length of the cob, cob diameter, cob relationship grain, 100 grain weight, yield per treatment, costs of production, utility and cost / benefit ratio. He placed a plant for blow at a distance of 80 x 20 cm (between rows and plant) whose population was 62,500 plants per hectare. Treatment with 46.50 gr T3 has the highest weight of 100 grains this treatment the hybrid 7088. DK was used, with a dose of 300 kg of urea per hectare. T4 treatment with 5924.22 kg ha-1 shows the increased production of maize per hectare of 18.28 t., in this treatment the hybrid DK 7088 was used with nitrogen doses of 350 kg of urea per hectare.